Displacement based fragility curves for R.C.C. frame structures in context of Dhaka, Bangladesh. - Manzur, Tanvir; Ahmed Noor, Munaz (2006)
In recent past, severe earthquakes have caused substantial physical losses and casualties in this sub-continent. At present Bangladesh is in high risk of attacked by earthquakes. Since a majority of the population is living in earthquake-prone areas, it is probable that such terrible events will take place again in the near future. Moreover, it is not easy to cope with the substantial direct and indirect economical losses after each devastating earthquake for a developing country like Bangladesh. Because in this country most of the reinforced concrete buildings are not designed according to the current building code, seismic behavior is not taken into consideration in the architectural design and during selection of the structural system and supervision in the construction phase is not adequate which in turn induces deficiencies like poor concrete quality, inadequate detailing of reinforcement etc. It is, therefore, vital to quantify the earthquake risk and to develop strategies for disaster mitigation. In order to achieve this goal, an extensive and inter-disciplinary study is required. Such a study is composed of two parts: hazard determination and vulnerability assessment. This study describes the methods by which it is possible to determine the vulnerability of existing engineering structures and building stock. The tool that is employed to assess the seismic performance of reinforced concrete frame structures is the fragility curve. By definition, fragility curves provide estimates for the probabilities of reaching or exceeding various limit states at given levels of ground shaking intensity for an individual structure or population of structures (MAE Report, 2003). A limit state; which is in the same terms as the response, usually represents a damage condition or a limitation of usage. The primary focus of this paper is to present a proper methodology that can be followed to construct fragility curves for R.C.C frame structures in Bangladesh and to generate fragility curves for some specific type of RCC frame structures using this methodology.